Peningkatan Kompetensi Digital dan Jiwa Sosial Siswa Melalui Pelatihan Pengkabelan Jaringan Komputer di SMA N 2 Kabupaten Sorong - Melda Agnes; Natasya Leuwol; Mayzer Mayzer; Yoma Yoma; Loksina Loksina; Viktor Viktor; Irwan Irwan; Sisin Sisin; Sonnya Sonnya; Susan Susan; Diki Diki (Lembaga Pengembangan Kinerja Dosen, 2026)
The training on computer network cabling serves not only to enhance students’ technical abilities but also to cultivate social values, collaborative behavior, and digital awareness within the school environment. The outreach activity conducted by students of Universitas Victory Sorong at SMA 2 Kabupaten Sorong aimed to strengthen students’ digital competence through the introduction of network devices and hands-on practice in creating LAN cables. The results indicate that this training effectively increased students’ understanding of computer network components, improved their practical skills in LAN cable assembly, and fostered cooperation and responsibility during group activities. From the perspective of Sociology of Education, the program contributed to the development of social capital by encouraging peer interaction, collaborative learning, and a deeper awareness of the role of technology in social life. This activity also addressed existing problems such as limited knowledge of network systems, lack of practical experience, and insufficient technology education in schools. Overall, the training led to improved technical comprehension, active participation, and enhanced social character formation. Therefore, computer network cabling training plays a significant role in promoting both digital literacy and social development among students in accordance with the principles of educational sociology.